Hereditary Hemorrhagic Telangiectasia or Osler-Weber -Rendu Syndrome: Management of Epistaxis in 4 Cases - H, Salina; PS, Lim; BS, Gendeh (IIUM Medical Journal Malaysia, 2020)
Hereditary Hemorrhagic Telangiectasia, also known as Osler-Weber-Rendu Syndrome is an autosomal dominant disorder causing systemic abnormalities of the vascular structure. There are multiple arteriovenous malformations present in the skin and mucosal surface of the nail beds, nose, gastrointestinal tract, lungs and brain. Epistaxis is the common presentation symptom, which may require multiple hospital admissions and blood transfusions. It is extremely rare disease in our population. We report 4 cases of HHT who presented to us with moderate to severe epistaxis and how we managed these patients.